The Effects of Traditional Concepts on Personal Values Among University Students in China - Song, Jun; Sun, Gong; Cai, Ruilin (Frontiers in Psychology, 2022)
It is widely agreed that China is experiencing a substantial transition toward modernization. However, both business behavior and day-to-day life in China are still greatly influenced and regulated by the traditional culture that has been embedded in Chinese society for thousands of years. Therefore, when studying social phenomena in China, researchers must take the indigenous cultural context into account. Focusing on the young generation in China, the authors explore the relationships between the most fundamental traditional concepts and various value dimensions. 332 university students in Southeast China took part in the survey and data were analyzed with SPSS. The result might help both scholars and practitioners to better understand the contemporary Chinese culture. The discussion and implications are also offered.